Assessment of induction technique and selection factors for agarwood production from cultivated aquilaria - Mat Desa, Mohamad Azren Putra (2021)
Aquilaria is a genus belonging to the Thymelaeaceae family. This genus produces the valuable, non-wood fragrant product known as agarwood (gaharu). Agarwood is a highly commercial non-timber product due to its important role in the fragrance, aromatherapy, and medicine industries, and its usage in religious activities. Along with the increasing agarwood demands and growth of Aquilaria plantations, some artificial methods to induce agarwood formation have been developed, not only to improve agarwood yields but also to produce sustainable agarwood with quality closely resembling the wild-sourced agarwood. In this study, an underrated method with high potential to increase agarwood yields were assessed in a field trial in a local plantation. Six cultivated Aquilaria subintegra trees were induced using a patented agarwood inducer, where three stands were harvested at six- and 12-months post induced, respectively, and were assessed (i.e., documenting agarwood formation, yields estimation and agarwood grading). It is shown that the inducer has the potential in maximizing the agarwood yields at 12 months post induced with higher quality than after six months post induced. A survey was conducted to evaluate the potential of agarwood inducer in local market. It highlighted five influential factors on inducer selection among smallholders/plantation owners. Chemical inducer has potential in local market since the desire to use chemical inducer among planters is about 48%. In addition, the trends of agarwood trade were found fluctuating but gives impression that the industry has potential to bring huge profits for planters and country. Overall, this study is informative and contribute analytical analysis for the advancement of agarwood industry.